Teacher Professional Responsibility and Student Respect in Indonesian Secondary Schools: An Emotion Regulation Perspective - Kasman, Apri (Edukasi, 2026)
Declining students’ respect toward teachers has become a growing concern in Indonesian secondary schools, particularly amid rapid social and cultural change. This study examines the relationship between students’ perceptions of teacher professional responsibility and their respectful behavior toward teachers. Using a quantitative survey design, data were collected from 300 students enrolled in vocational and general secondary schools in Indonesia. A Likert-scale questionnaire measured students’ perceptions of respectful behavior and three dimensions of teacher professional responsibility: instructional, ethical, and relational. Data were analyzed using descriptive statistics and Pearson correlation analysis. The findings indicate that 62.7% of students demonstrated moderate to low levels of respectful behavior, particularly in verbal conduct and adherence to classroom norms. Most students (68.4%) perceived teacher professional responsibility primarily in terms of instructional delivery rather than ethical guidance or relational engagement. Correlational analysis revealed a significant positive relationship between students’ perceptions of teachers’ ethical and relational responsibility and their respectful behavior (r = 0.49, p < .001). In contrast, perceptions limited to instructional competence showed a weaker association with students’ respect. These results suggest that professional responsibility defined by ethical consistency and relational engagement is more strongly associated with students’ respect than responsibility framed solely as instructional competence. The study highlights the importance of integrating ethical and relational dimensions into teacher professional development and school policy to strengthen respectful classroom interactions in Indonesian secondary education.